Moderation and Envisioned Civilization: The Interplay Between Rationality, Morality, Spirituality - Abdullah, Mujaddid bin (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2024)
The triumph of Western civilization which marked bysignificant industrial revolution through scientific breakthroughs andtechnological advancements still not necessarily make this civilizationbetter as expected. With strongly emphasis on its pursuit ofrationality, this civilization has faced criticism from numerousexperts due to its various deficiencies and subsequent detrimentalconsequences. This article will investigate on how the notion of